Electrolyte, battery, battery pack, electric device

CN123018135APending Publication Date: 2026-10-30BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510577892.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,传统电解液在宽电压使用范围内容易发生分解产气,劣化电池的循环性能和存储性能

Benefits of technology

[0029]本发明第三方面提供一种电池组,所述电池组包括至少两个第二方面所述的电池。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005389447380000191
    Figure BDA0005389447380000191
  • Figure BDA0005389447380000201
    Figure BDA0005389447380000201
  • Figure BDA0005389447380000211
    Figure BDA0005389447380000211
Patent Text Reader

Abstract

The application provides an electrolyte, a battery, a battery pack and an electric device, the electrolyte comprising a lithium salt, an organic solvent and an additive; the additive comprises an unsaturated carbonate additive, a sulfur additive, a bifluoride lithium salt additive and an unsaturated phosphate additive; the mass content of each additive in the electrolyte is controlled, and the mass content of each additive satisfies: y=0.35b 2 -2.10b+4.04, and 0.89<=y<=3.2, wherein b is the total mass content of the additive in the electrolyte, in %. The electrolyte can effectively improve the cycle performance and storage performance of the battery and reduce the gas production of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery technology, and relates to an electrolyte, and more particularly to an electrolyte, a battery, a battery pack, and an electrical device. Background Technology

[0002] Lithium-ion batteries are widely used in various fields due to their advantages such as low self-discharge rate, no memory effect, strong adaptability to high and low temperatures, and environmental friendliness, including electric bicycles, electric vehicles, portable electronic devices, aerospace, industrial power systems, and energy storage systems. With continuous technological development and progress, users are placing higher demands on the battery life of their devices, and the energy density of batteries is closely related to the battery life of these devices.

[0003] The energy density (Wh / kg) of a battery is determined by both voltage (V) and capacity (mAh / g). Therefore, increasing the charging voltage of the cathode material or developing a high-voltage cathode is a key approach to improving energy density. However, traditional electrolytes are prone to decomposition and gas generation over a wide voltage operating range, which degrades the battery's cycle performance and storage performance.

[0004] Therefore, it is necessary to improve the electrolyte to reduce gas production and improve the battery's cycle and storage performance. Summary of the Invention

[0005] To address the aforementioned shortcomings, this invention provides an electrolyte that exhibits high stability under high voltage conditions, effectively reducing battery gas production and improving battery cycle and storage performance.

[0006] The present invention also provides a battery comprising the above-described electrolyte, thereby the battery having a lower gas production rate and higher cycle performance and storage performance.

[0007] The present invention also provides a battery pack comprising the above-described battery, thereby having a lower gas production rate and higher cycle performance and storage performance.

[0008] The present invention also provides an electrical device, which includes the above-mentioned battery or battery pack, and therefore the electrical device has good battery life and service life.

[0009] The first aspect of the present invention provides an electrolyte comprising a lithium salt, an organic solvent, and additives; the additives include unsaturated carbonate additives, sulfur-based additives, lithium difluorophosphate additives, and unsaturated phosphate additives.

[0010] Based on the total mass of the electrolyte, the mass content m1% of the unsaturated carbonate additives satisfies: 0.35≤m1≤3.0, the mass content m2% of the sulfur-based additives satisfies: 0.01≤m2≤1.5, the mass content m3% of the lithium difluoride salt additives satisfies: 0<m3≤1.0, and the mass content m4% of the phosphate ester additives satisfies: 0.01≤m4≤0.8.

[0011] The electrolyte satisfies: y = 0.35b 2 -2.10b+4.04, and 0.89≤y≤3.2, where b is the total mass content of the additive in the electrolyte, in percentages (%).

[0012] The electrolyte as described above, wherein 1.5≤m1≤3.0, and / or, 0.5≤m2≤1.5, and / or, 0.5≤m3≤1.0, and / or, 0.3≤m4≤0.8, and / or, 0.89≤y≤2.0.

[0013] In the electrolyte described above, the unsaturated carbonate additive includes vinylene carbonate;

[0014] And / or, the sulfur-based additives include at least one of methylene disulfonate, vinyl sulfate, 1,3-propenesulfonate lactone, and propylene sulfite.

[0015] And / or, the lithium difluorophosphate additive includes at least one of lithium difluorophosphate, lithium difluorosulfonylimide, and lithium difluorooxalate phosphate;

[0016] And / or, the unsaturated phosphate additives include triargyl phosphate and / or triallyl phosphate.

[0017] The electrolyte as described above, wherein the additives further include fluorocarbonate additives and / or cyclic carbonate additives;

[0018] Preferably, the fluorocarbonate additives include fluoroethylene carbonate and / or fluoroethylene carbonate;

[0019] Preferably, the cyclic carbonate additive includes ethylene carbonate.

[0020] In the electrolyte as described above, the mass content m5% of the fluorocarbonate additives and / or cyclic carbonate additives, based on the total mass of the electrolyte, satisfies the following condition: 0 < m5 ≤ 0.5.

[0021] The electrolyte as described above, wherein 0.35% ≤ b ≤ 4.7%.

[0022] The electrolyte as described above, wherein the lithium salt comprises lithium hexafluorophosphate; preferably, the lithium salt further comprises lithium bis(trifluoromethanesulfonyl)imide and / or lithium dioxaborate; preferably, the mass content of the lithium salt in the electrolyte is 12% to 15%.

[0023] The electrolyte as described above, wherein the organic solvent includes a first carbonate solvent; preferably, the first carbonate solvent includes ethylene carbonate.

[0024] In the electrolyte as described above, the organic solvent has a mass content of 80% to 86% in the electrolyte; and / or, the ethylene carbonate has a mass content of 20% to 30% in the electrolyte.

[0025] The electrolyte as described above, wherein the organic solvent further includes a second carbonate solvent, the second carbonate solvent including at least one of ethyl methyl carbonate, dimethyl carbonate, and diethyl carbonate.

[0026] A second aspect of the present invention provides a battery comprising the electrolyte described in the first aspect.

[0027] The battery as described above further includes a positive electrode sheet, which comprises a positive electrode active material; the positive electrode active material comprises a ternary material and a lithium manganese iron phosphate material; preferably, the mass ratio of the ternary material to the lithium manganese iron phosphate material is 2:8 to 8:2.

[0028] The battery as described above further includes a negative electrode sheet, the negative electrode sheet comprising a negative electrode active material; the negative electrode active material comprises a carbon-based negative electrode material, the carbon-based negative electrode material comprising at least one of artificial graphite, natural graphite, hard carbon, soft carbon, and mesophase carbon microspheres.

[0029] A third aspect of the present invention provides a battery pack comprising at least two batteries as described in the second aspect.

[0030] A fourth aspect of the present invention provides an electrical device, the electrical device comprising the battery described in the second aspect or the battery pack described in the third aspect.

[0031] This invention comprises unsaturated carbonate additives, sulfur-based additives, difluorolithium salt additives, and unsaturated phosphate ester additives in the electrolyte, while simultaneously controlling the mass content of each additive in the electrolyte to ensure that the mass content of each additive satisfies: y = 0.35b 2 -2.10b+4.04, 0.89≤y≤3.2, where b is the total mass content of the additive in the electrolyte, in %, to effectively improve the battery's cycle performance, storage performance and reduce gas production. Detailed Implementation

[0032] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0033] The first aspect of this invention provides an electrolyte comprising a lithium salt, an organic solvent, and additives; the additives include unsaturated carbonate additives, sulfur-based additives, lithium difluoride salt additives, and unsaturated phosphate ester additives; based on the total mass of the electrolyte, the mass content m1% of the unsaturated carbonate additives satisfies: 0.35≤m1≤3.0, the mass content m2% of the sulfur-based additives satisfies: 0.01≤m2≤1.5, the mass content m3% of the lithium difluoride salt satisfies: 0<m3≤1.0, and the mass content m4% of the unsaturated phosphate ester additives satisfies: 0.01≤m4≤0.8; the electrolyte satisfies: y=0.35b 2 -2.10b+4.04, and 0.89≤y≤3.2, where b is the total mass content of the additive in the electrolyte, in percentage.

[0034] For example, m1 can be 0.35, 0.5, 0.7, 1, 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, or a range of any two values ​​therein; m2 can be 0.01, 0.1, 0.2, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1 0.5 or any two of these values; m3 can be a range of 0.001, 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0 or any two of these values; m4 can be a range of 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or any two of these values.

[0035] For example, the value of y can be 0.89, 0.9, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2 or a range of any two of these values.

[0036] For example, when m1 is 2.0, m2 is 1.0, m3 is 0.8, and m4 is 0.5, b = m1 + m2 + m3 + m4 = 2.0 + 1.0 + 0.8 + 0.5 = 4.3%, then b = 4.3. Substituting b into y = 0.35b2 From -2.10b+4.04, we obtain y = 0.35 × 4.3. 2 -2.10×4.3+4.04=1.48, which satisfies 0.89≤y≤3.2.

[0037] This invention does not specifically limit the source of each component in the electrolyte; any commercially available product or product prepared by conventional methods well known to those skilled in the art can be used.

[0038] The electrolyte in this invention includes unsaturated carbonate additives, sulfur-based additives, difluorinated lithium salt additives, and unsaturated phosphate ester additives. When the mass content of these four additives in the electrolyte is controlled to meet the above-mentioned range and the above-mentioned relationship, the four additives can synergistically improve the battery's storage performance and cycle performance under high voltage, and reduce battery gas production. The inventors, after analysis, believe the reason is:

[0039] Unsaturated carbonate additives contain unsaturated carbon-carbon bonds, which can be reduced on the negative electrode surface and form a cross-linked polycarbonate network through ring-opening polymerization. This network, along with inorganic components (such as LiCO3), forms a relatively dense and uniform SEI film, suppressing side reactions between the electrolyte and the electrode and reducing gas generation due to solvent molecule decomposition. Furthermore, the formed SEI film possesses a certain degree of toughness, constraining the expansion and contraction of the negative electrode active particles during charging and discharging, reducing the pulverization of the active material and the rupture of the SEI film. Based on this, sulfur-based additives can oxidize on the positive electrode surface to form a sulfur-containing inorganic-organic composite CEI film, inhibiting the dissolution of transition metals (such as Mn and Co) in the positive electrode active material, reducing the risk of positive electrode structural collapse, minimizing capacity decay, and reducing electrolyte oxidation and gas generation under high voltage.

[0040] However, the SEI film formed by unsaturated carbonate additives has a large impedance, and the unsaturated carbonate additives will generate gas (mainly CO2) during the film formation process, which will have a negative impact on the cycle performance and storage performance of the battery.

[0041] By including unsaturated phosphate ester additives in the electrolyte, gas production can be significantly suppressed, thus improving the battery's storage performance. The inventors, after analysis, believe the reason may be that unsaturated carbonate additives may generate free radical intermediates (such as CH2CH2OCO2) during decomposition. - These free radicals can trigger chain reactions, exacerbating gas production. However, the unsaturated carbon-carbon bonds in unsaturated phosphate ester additives can act as free radical acceptors, terminating the free radical chain reaction through addition reactions and reducing gas generation. Simultaneously, the introduction of phosphate esters may alter the decomposition pathway of unsaturated carbonate additives, making them more likely to produce solid products (such as polycarbonate) rather than gaseous products.

[0042] Meanwhile, this invention effectively reduces interfacial impedance by including lithium difluoride salt additives in the electrolyte. This is because lithium difluoride salt additives tend to form SEI films rich in inorganic components, such as LiF. LiF has a high lithium-ion transference number, and its grain boundary structure provides a fast diffusion channel for lithium ions, thereby reducing the ion transport impedance of the SEI film. Furthermore, lithium difluoride salt additives can make the SEI film structure more compact, reducing the path resistance for lithium-ion diffusion across the film. Therefore, impedance can be effectively reduced, and the cycle performance of the battery can be improved.

[0043] Furthermore, it is necessary to further control the mass content of various additives in the electrolyte to better balance the effects of each additive in the battery and achieve better synergy. Through extensive research, the inventors discovered that when the mass content of various additives in the electrolyte is within the aforementioned range and satisfies the above-mentioned relationship, it can comprehensively improve the battery's cycle performance, storage performance, and reduce gas production.

[0044] It should be noted that the presence of the aforementioned additives in the battery electrolyte can be determined using the following methods:

[0045] The fully discharged battery is disassembled to obtain the positive and negative electrode sheets. These are then soaked and cleaned with dimethyl carbonate (DMC) or ethanol to remove residual electrolyte and lithium salt. XPS testing is performed on the positive and negative electrode sheets to determine the main components of the CEI film on the surface of the positive electrode and the SEI film on the surface of the negative electrode. Based on the analysis of the tested components, the specific types of additives included in the electrolyte can be determined.

[0046] For example, when the unsaturated carbonate additive is vinylene carbonate (VC), the film-forming product of VC in the SEI film is mainly polyvinyl carbonate. When the sulfur-based additive includes at least one of vinyl sulfate (DTD), 1,3-propenesulfonate lactone (PST), methanedisulfonate methylene (MMDS), and propylene sulfite (PS), the film-forming product of DTD in the SEI film is mainly Li₂SO₄, that of PST is mainly sulfonate, that of MMDS is mainly Li₂SO₃, and that of PS is mainly C₃H₇OSO₂Li. When the difluorolithium salt additive includes at least one of lithium difluorophosphate, lithium difluorosulfonylimide, and lithium difluorooxalate phosphate, the film-forming products of lithium difluorophosphate and lithium difluorooxalate phosphate in the SEI film are mainly Li₂SO₄. x PO y F z(x+5=2y+z), the film-forming product of lithium bis(fluorosulfonyl)imide in the SEI film is mainly LiF. When unsaturated phosphate ester additives include triargyl phosphate (TPP) and triallyl phosphate (TAPP), their film-forming products in the SEI film are mainly phosphate ester oligomers.

[0047] The mass content of each component (including organic solvent, lithium salt, and additives) in the electrolyte of this invention is tested by conventional methods in the art. For example, it can be obtained by combining multiple methods, including inductively coupled plasma spectroscopy (ICP-OES / MS), ion chromatography (IC), gas chromatography (GC), nuclear magnetic resonance (NMR), high performance liquid chromatography (HPLC), and ultraviolet-visible spectrophotometry (UV-Vis).

[0048] Furthermore, the components and content of the electrolyte can be controlled to give the battery higher storage and cycle performance.

[0049] In one specific embodiment, 1.5 ≤ m1 ≤ 3.0, 0.5 ≤ m2 ≤ 1.5, 0.5 ≤ m3 ≤ 1.0, 0.3 ≤ m4 ≤ 0.8, and / or, 0.89 ≤ y ≤ 2.0. Within this range, the additives in the electrolyte can work synergistically to further suppress gas generation and improve the battery's storage and cycle performance.

[0050] In one specific embodiment, the unsaturated carbonate additives include vinylene carbonate; the sulfur-based additives include at least one of methanedisulfonate, vinyl sulfate, 1,3-propenesulfonate lactone, and propylene sulfite; the difluorolithium salts include at least one of lithium difluorophosphate, lithium difluorosulfonylimide, and lithium difluorooxalate phosphate; and the unsaturated phosphate additives include triargyl phosphate and / or triallyl phosphate.

[0051] When the aforementioned four types of additives each include the aforementioned specific compounds, they can work synergistically to further suppress gas production and improve the battery's storage and cycle performance.

[0052] It should be noted that when the aforementioned four types of additives (unsaturated carbonate additives, sulfur-based additives, lithium difluorophosphate additives, and unsaturated phosphate ester additives) are mixtures of the specific compounds listed above, the present invention does not impose specific limitations on the proportions between the individual compounds. For example, when the sulfur-based additives simultaneously include methylene methane disulfonate (MMDS), vinyl sulfate (DTD), propylene sulfite (PS), and 1,3-propenesulfonate lactone (PST), the present invention does not impose specific limitations on the proportions between the four.

[0053] In one specific embodiment, the additive further includes fluorocarbonate additives and / or cyclic carbonate additives; preferably, the fluorocarbonate additives include fluoroethylene carbonate and / or difluoroethylene carbonate; preferably, the cyclic carbonate additives include ethylene ethylene carbonate.

[0054] In detail, the additives also include fluorocarbonate additives, or the additives also include cyclic carbonate additives, or the additives also include both fluorocarbonate additives and cyclic carbonate additives.

[0055] Fluorinated carbonate additives can synergistically work with unsaturated carbonate additives to make the SEI film structure more compact, reduce the continuous decomposition of the electrolyte, and lower the impedance caused by side reactions. Simultaneously, the strong electronegativity of fluorine atoms can modulate the electron / ion transport characteristics of the SEI film, further reducing impedance and improving battery cycle performance. Cyclic carbonate additives can synergistically work with fluorinated additives (including fluorinated carbonate additives and difluorinated lithium salt additives) to form LiF-polymer composite SEIs, which not only enhance the elasticity of the SEI film but also possess high ionic conductivity and chemical stability.

[0056] It should be noted that when the additives include both fluorocarbonate additives and cyclic carbonate additives, the present invention does not impose a specific limit on the ratio between the two.

[0057] In one specific embodiment, based on the total mass of the electrolyte, the mass content m5% of fluorocarbonate additives and / or cyclic carbonate additives satisfies: 0 < m5 ≤ 0.5. More specifically, the mass content m5% of fluorocarbonate additives in the electrolyte satisfies: 0 < m5 ≤ 0.5, or the mass content m5% of cyclic carbonate additives in the electrolyte satisfies: 0 < m5 ≤ 0.5, or the total mass content m5% of fluorocarbonate additives and cyclic carbonate additives in the electrolyte satisfies: 0 < m5 ≤ 0.5. Within this range, battery impedance can be further reduced, and battery cycle performance can be improved.

[0058] For example, m5 can be 0.001, 0.01, 0.1, 0.2, 0.3, 0.4, 0.5 or a range of any two of these values.

[0059] In one specific embodiment, 0.35% ≤ b ≤ 4.7%. Within this range, the mass content of additives in the electrolyte is moderate, which can further reduce gas production and lower impedance, giving the battery higher storage and cycle performance.

[0060] For example, b can be 0.35%, 0.5%, 1%, 1.5%, 2%, 2.5%, 2.5%, 3%, 3.5%, 4%, 4.5%, 4.7%, or a range of any two of these values.

[0061] In one specific embodiment, the lithium salt includes lithium hexafluorophosphate; preferably, the lithium salt further includes lithium bis(trifluoromethanesulfonyl)imide and / or lithium dioxaborate; preferably, the mass content of the lithium salt in the electrolyte is 12% to 15%.

[0062] When the lithium salt in the electrolyte is mainly LiPF6, the electrolyte can have good conductivity. Furthermore, when the lithium salt also includes the aforementioned specific lithium salts, the stability of the electrolyte can be improved to a certain extent. Even further, when the mass content of lithium salt in the electrolyte is within the aforementioned range, the electrolyte can have high conductivity and ensure the stability of the electrolyte.

[0063] For example, the mass content of lithium salt in the electrolyte can be 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, or any two of these values.

[0064] It should be noted that when the lithium salt includes lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium dioxaborate (LiBOB), the present invention does not specifically limit the ratio between the three or the mass content of each of the three in the electrolyte, as long as the mass content of the lithium salt in the electrolyte is within the aforementioned range.

[0065] In one specific embodiment, the organic solvent includes a first carbonate solvent; preferably, the first carbonate solvent includes ethylene carbonate. When the organic solvent is mainly a carbonate solvent, this type of solvent can not only promote the dissociation of lithium salt to form an electrolyte with high ionic conductivity, but also has high antioxidant capacity, making it suitable for high-voltage cathode systems; at the same time, it also has low viscosity and high fluidity, which helps to improve lithium-ion migration efficiency and reduce battery polarization; in addition, it has good temperature adaptability and can operate stably over a wide temperature range. Ethylene carbonate (EC) has more prominent advantages compared to other types of carbonate solvents. EC has a large dielectric constant and can participate in the formation of SEI film, which helps to improve the cycle performance of the battery.

[0066] In one specific embodiment, the organic solvent has a mass content of 80% to 86% in the electrolyte. Within this range, it helps to balance solvent volatility and lithium salt solubility, control the water content in the electrolyte, and also reduces gas generation under high temperature and high pressure, thereby improving the battery's storage performance. At the same time, it can also optimize interface stability and ion transport efficiency, which helps to improve the battery's cycle performance.

[0067] For example, the mass content of the organic solvent in the electrolyte can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, or any two of these values.

[0068] In one specific embodiment, the mass content of ethylene carbonate in the electrolyte is 20% to 30%. When the mass content of EC in the electrolyte is within the aforementioned range, the electrolyte can have a relatively suitable viscosity, which is conducive to lithium ion migration and improves the cycle performance of the battery.

[0069] For example, the mass content of EC in the electrolyte is 20%, 22%, 24%, 26%, 28%, 30%, or any two of these values.

[0070] In one specific embodiment, the organic solvent further includes a second carbonate solvent, which includes at least one of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and diethyl carbonate (DEC). When the electrolyte includes EC, the inclusion of the aforementioned carbonate solvent can further improve the ion transport performance of the electrolyte, resulting in higher cycle performance of the battery.

[0071] When the electrolyte contains EMC, DMC and DEC, the present invention does not specify the ratio between the three.

[0072] The present invention does not impose any special limitation on the mass content of the above-mentioned EMC, DMC or DEC in the electrolyte, and can be adjusted according to the actual situation.

[0073] In one specific embodiment, the organic solvent further includes fluorinated ether solvents and / or carboxylic acid ester solvents. Fluorinated ether solvents are characterized by high voltage resistance and can improve the oxidation resistance of the electrolyte; carboxylic acid ester solvents can further reduce the viscosity of the electrolyte and improve its ionic conductivity.

[0074] In detail, organic solvents also include fluorinated ether solvents, or organic solvents include carboxylic acid ester solvents, or organic solvents include both fluorinated ether solvents and carboxylic acid ester solvents.

[0075] This invention does not specifically limit the types of fluorinated ether solvents and carboxylic acid ester solvents. They can be fluorinated ether solvents and carboxylic acid ester solvents commonly used in battery electrolytes. For example, fluorinated ether solvents include bis(2,2,2-trifluoroethyl) ether and / or 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, and carboxylic acid ester solvents include at least one of ethyl acetate, ethyl propionate, and ethyl butyrate.

[0076] When the organic solvent includes both fluorinated ether solvents and carboxylic acid ester solvents, the present invention does not impose a specific limit on the ratio between the two.

[0077] A second aspect of the present invention provides a battery comprising the electrolyte of the first aspect. This battery has effects corresponding to the electrolyte, which will not be elaborated here.

[0078] In one specific embodiment, the battery further includes a positive electrode sheet, which includes a positive electrode active material; the positive electrode active material includes a ternary material and a lithium manganese iron phosphate material; preferably, the mass ratio of the ternary material and the lithium manganese iron phosphate material is 2:8 to 8:2.

[0079] Compared to other active materials, ternary materials have higher energy density, with a theoretical specific capacity of 200 mAh / g to 220 mAh / g (2.8V to 4.3V). However, their thermal stability is poor, and they are prone to structural collapse and dissolution of transition metal ions under high voltage and high temperature, leading to capacity decay. Lithium manganese iron phosphate (LFP), on the other hand, has an olivine structure and is more structurally stable. By blending ternary materials and LFP, not only can the volume change of the ternary material be suppressed during cycling, and the accumulation of lattice stress be slowed, but the direct contact between the electrolyte and the ternary material can also be reduced, suppressing side reactions between the electrolyte and the ternary material under high voltage, reducing gas production. Furthermore, the CEI film formed on the surface of LFP can adsorb metal ions dissolved from the ternary material, thereby reducing the damage of metal ions to the SEI. Therefore, when using a mixture of ternary materials and LFP as the positive electrode active material, a balance between energy density, storage performance, and cycling performance can be achieved.

[0080] When the mass ratio of ternary materials to lithium manganese iron phosphate is within the aforementioned range, the storage performance and cycle performance of the battery can be further improved.

[0081] For example, the mass ratio of ternary material to lithium manganese iron phosphate material can be 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 or any two of these ratios.

[0082] The present invention does not impose any special limitations on the structure of the positive electrode sheet. In one embodiment, the positive electrode sheet includes a positive current collector and a positive active layer disposed on at least one side of the positive current collector. The positive active layer includes a positive active material, which includes ternary materials and lithium manganese iron phosphate materials.

[0083] The present invention does not specifically limit the material of the positive electrode current collector, and can be any conventional choice in the art, such as aluminum foil or nickel foil.

[0084] It is understood that the positive electrode active layer also includes a binder and a conductive agent, which can be the binders and conductive agents commonly used in lithium-ion batteries. The conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber; the binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinylpyrrolidone, and polyurethane.

[0085] This invention does not impose specific limitations on the proportions of each component in the positive electrode active layer; appropriate ratios can be selected based on actual conditions.

[0086] This invention does not specifically limit the preparation method of the positive electrode sheet. In one embodiment, it can be prepared by the following method:

[0087] The positive electrode active material, conductive agent, and binder are dispersed in an appropriate amount of solvent (such as N-methylpyrrolidone (NMP)) and thoroughly stirred to form a uniform positive electrode slurry. The positive electrode slurry is then uniformly coated onto the positive electrode current collector, and after drying, rolling, and slitting, a positive electrode sheet is obtained.

[0088] In one specific embodiment, the battery further includes a negative electrode sheet, which comprises a negative electrode active material; the negative electrode active material includes a carbon-based negative electrode material, wherein the carbon-based negative electrode material includes at least one of artificial graphite, natural graphite, hard carbon, soft carbon, and mesophase carbon microspheres. When the negative electrode active material includes a carbon-based negative electrode material, or further includes the aforementioned specific carbon-based negative electrode material, the volume expansion of the negative electrode active material during charge and discharge processes can be reduced, side reactions can be reduced, gas production can be reduced, and the cycle performance and storage performance of the battery can be further improved.

[0089] The present invention does not specifically limit the structure of the negative electrode sheet. In one embodiment, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least one side of the negative electrode current collector. The negative electrode active layer includes a negative electrode active material, which includes a carbon-based negative electrode material.

[0090] The present invention does not specifically limit the material of the negative electrode current collector, and can be any of the conventional choices in the art, such as copper foil, nickel foam, and copper foam.

[0091] It is conceivable that the negative electrode active layer also includes a binder and a conductive agent, which can be the binders and conductive agents commonly used in lithium-ion batteries. For example, the conductive agent can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and graphene; the binder can be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate.

[0092] This invention does not impose specific limitations on the proportions of each component in the negative electrode active layer; appropriate ratios can be selected based on actual conditions.

[0093] This invention does not specifically limit the preparation method of the negative electrode sheet. In one embodiment, it can be prepared by the following method:

[0094] The negative electrode active material, conductive agent, and binder are dispersed in an appropriate amount of solvent (such as deionized water) and thoroughly stirred to form a uniform negative electrode slurry. The negative electrode slurry is then uniformly coated onto the negative electrode current collector, and after drying, rolling, and slitting, a negative electrode sheet is obtained.

[0095] It is understood that, in addition to the positive electrode, electrolyte, and negative electrode mentioned above, a separator is generally also included in the battery. This invention does not impose any special limitations on the material of the separator; it can be any separator material commonly used in lithium-ion batteries. For example, it can be selected from any of the following: polypropylene separator (PP), polyethylene separator (PE), polypropylene / polyethylene bilayer composite membrane (PP / PE), polyimide electrospun separator (PI), polypropylene / polyethylene / polypropylene trilayer composite membrane (PP / PE / PP), cellulose nonwoven fabric separator, and separator with ceramic coating.

[0096] This invention does not specifically limit the preparation method of lithium-ion batteries, which can be prepared by conventional methods in the art; in one embodiment, they can be prepared by the following method;

[0097] The positive electrode, separator, and negative electrode are stacked to obtain a bare cell, and the bare cell is packaged into a pre-stamped aluminum-plastic film bag. After the packaged battery is dried, the electrolyte of the present invention is injected into the dried battery. After the battery is placed, formed, and resealed, the lithium-ion battery is completed.

[0098] A third aspect of the present invention provides a battery pack comprising at least two batteries according to the second aspect. This battery pack has the same effects as the batteries described above, which will not be elaborated upon here.

[0099] Generally, a battery pack includes multiple (at least two) of the aforementioned batteries, which are connected as individual cells to form the battery pack. These batteries can be electrically connected using methods conventional in the art, such as series connection, parallel connection, or a hybrid connection including both of these methods, without any particular limitation.

[0100] A fourth aspect of the present invention provides an electrical device comprising a battery as described in the second aspect or a battery pack as described in the third aspect. This electrical device has good battery life and a long service life.

[0101] In this invention, there are no particular limitations on the electrical devices that use the aforementioned batteries or battery packs. Exemplarily, the aforementioned electrical devices include, but are not limited to, mobile phones, laptops, tablets, cameras, televisions, radios, wearable devices (such as smartwatches, smart bracelets, stereo headphones, Bluetooth headsets), electric vehicles (such as new energy vehicles, electric bicycles, etc.), electric toys, backup power supplies, and large household batteries.

[0102] The electrolyte and battery including the electrolyte provided by the present invention will be described in detail below through specific embodiments.

[0103] Example 1

[0104] 1) Preparation of positive electrode sheet

[0105] Lithium manganese iron phosphate (chemical formula LiFe) 0.4 Mn 0.6 PO4) and ternary materials (chemical formula LiNi) 0.7 Co 0.1 Mn 0.2 O2) was uniformly mixed at a mass ratio of 8:2 to form the positive electrode active material; the aforementioned positive electrode active material, binder polyvinylidene fluoride (PVDF), conductive agent carbon black, and carbon nanotubes were added to NMP at a mass ratio of 95.5:2:1.5:1 and mixed uniformly to prepare a positive electrode slurry; the positive electrode slurry was coated onto aluminum foil, and after baking and rolling, the positive electrode sheet of this embodiment was obtained, with a double-sided areal density of 4 g / cm³. 2 The compacted density is 2.6 g / cm³. 3 .

[0106] 2) Preparation of negative electrode sheet

[0107] Artificial graphite (anode active material), styrene-butadiene rubber (SBR) (binder), carboxymethyl cellulose (CMC) (thickener), and carbon black (conductive agent) were added to water at a mass ratio of 94.5:2:1.5:2 and mixed evenly to obtain a cathode slurry. This cathode slurry was then coated onto copper foil, and after baking and rolling, the cathode sheet of this embodiment was obtained, with a double-sided areal density of 1.8 g / cm³. 2The compacted density is 1.6 g / cm³. 3 .

[0108] 3) Preparation of electrolyte

[0109] In an argon-filled glove box, 13% lithium hexafluorophosphate (LiPF6) based on the total mass of the electrolyte was dissolved in 30% ethylene carbonate (EC) and 53% methyl ethyl carbonate (EMC) based on the total mass of the electrolyte. Then, 2% vinylene carbonate (VC), 1% methanedisulfonate (MMDS), 0.5% triallyl phosphate (TAPP), and 0.5% lithium difluorophosphate (LiPO2F2) based on the total mass of the electrolyte were added to obtain the electrolyte of this embodiment.

[0110] 4) Battery manufacturing

[0111] The above-mentioned positive electrode sheet, PP separator, and negative electrode sheet are wound to obtain a bare cell, and the bare cell is packaged into a pre-stamped aluminum-plastic film bag. After drying the packaged battery, the above-mentioned electrolyte is injected into the dried battery. After the battery is placed, formed, and resealed, the lithium-ion battery is completed. The designed capacity of the battery is 1.7Ah. The formation mechanism is as follows: constant current charging at 0.05C for 4 hours, constant current charging at 0.2C for 3 hours, constant current and constant voltage charging at 0.33C to 4.3V, and the cut-off current is 0.05C. The capacity grading mechanism is as follows: constant current and constant voltage charging at 0.33C to 4.3V, cut-off current at 0.05C, placed for 10 minutes, and then constant current discharging at 0.33C to 2.5V.

[0112] Example 2

[0113] The battery preparation method in this embodiment is basically the same as that in embodiment 1. The difference is that in step 3), based on the total mass of the electrolyte, the mass content of EMC is 52.5% and the mass content of VC is 2.5%.

[0114] Example 3

[0115] The battery preparation method in this embodiment is basically the same as that in embodiment 1. The difference is that in step 3), based on the total mass of the electrolyte, the mass content of EMC is 53.5% and the mass content of VC is 1.5%.

[0116] Example 4

[0117] The battery preparation method in this embodiment is basically the same as that in embodiment 1. The difference is that in step 3), based on the total mass of the electrolyte, the mass content of EMC is 53.5% and the mass content of MMDS is 0.5%.

[0118] Example 5

[0119] The battery preparation method in this embodiment is basically the same as that in Example 1. The difference is that in step 3), based on the total mass of the electrolyte, the mass content of EMC is 53.5% and the mass content of VC is 1.5%, and TAPP is replaced with triargyl phosphate (TPP).

[0120] Example 6

[0121] The battery preparation method in this embodiment is basically the same as that in embodiment 5. The difference is that in step 3), based on the total mass of the electrolyte, the mass content of EMC is 52.5%, the mass content of VC is 3%, and the mass content of MMDS is 0.5%.

[0122] Example 7

[0123] The battery preparation method in this embodiment is basically the same as that in Example 1. The difference is that in step 3), MMDS is replaced with ethylene sulfate (DTD), LiPO2F2 is replaced with lithium bis(fluorosulfonyl)imide (LiFSI), and TAPP is replaced with TPP.

[0124] Example 8

[0125] The battery preparation method in this embodiment is basically the same as that in Example 1. The difference is that in step 3), MMDS is replaced with 1,3-propenesulfonate lactone (PST), LiPO2F2 is replaced with lithium difluorooxalate phosphate (LiDODFP), and TAPP is replaced with TPP.

[0126] Example 9

[0127] The battery preparation method in this embodiment is basically the same as that in embodiment 1. The difference is that in step 3), MMDS is replaced with PS, LiPO2F2 is replaced with lithium difluorooxalate phosphate (LiDODFP), and TAPP is replaced with TPP.

[0128] Example 10

[0129] The battery preparation method in this embodiment is basically the same as that in embodiment 1. The difference is that in step 3), based on the total mass of the electrolyte, the mass content of EMC is 52.7%, the mass content of VC is 1.5%, the mass content of MMDS is 1.5%, the mass content of LiPO2F2 is 0.5%, and the mass content of TAPP is 0.8%.

[0130] Example 11

[0131] The battery preparation method in this embodiment is basically the same as that in embodiment 1. The difference is that in step 3), based on the total mass of the electrolyte, the mass content of EMC is 52.7%, the mass content of LiPO2F2 is 1%, and the mass content of TAPP is 0.3%.

[0132] Example 12

[0133] The battery preparation method in this embodiment is basically the same as that in Example 1. The difference is that in step 3), fluoroethylene carbonate (FEC) is added to the electrolyte. Based on the total mass of the electrolyte, the mass content of FEC is 0.1% and the mass content of EMC is 53.4%.

[0134] Example 13

[0135] The battery preparation method in this embodiment is basically the same as that in embodiment 12. The difference is that in step 3), based on the total mass of the electrolyte, the mass content of FEC is 0.5% and the mass content of EMC is 53%.

[0136] Example 14

[0137] The battery preparation method in this embodiment is basically the same as that in Example 12, except that in step 3), FEC is replaced with ethylene ethylene carbonate (VEC). Based on the total mass of the electrolyte, the mass content of VEC is 0.3% and the mass content of EMC is 53.2%.

[0138] Example 15

[0139] The battery preparation method in this embodiment is basically the same as that in Example 1, except that in step 1), the mass ratio of lithium manganese iron phosphate to ternary material is 2:8.

[0140] Example 16

[0141] The battery preparation method in this embodiment is basically the same as that in Example 1, except that in step 1), the mass ratio of lithium manganese iron phosphate and ternary material is 5:5.

[0142] Example 17

[0143] The battery preparation method in this embodiment is basically the same as that in Example 12. The difference is that in step 3), based on the total mass of the electrolyte, the mass content of FEC is 0.7% and the mass content of EMC is 52.5%.

[0144] Example 18

[0145] The battery preparation method in this embodiment is basically the same as that in Example 1, except that in step 3), MMDS is replaced with vinyl sulfite (ES).

[0146] Example 19

[0147] The battery preparation method in this embodiment is basically the same as that in embodiment 1, except that in step 3), LiPO2F2 is replaced with lithium difluorooxalate borate (LiODFB).

[0148] Example 20

[0149] The battery preparation method in this embodiment is basically the same as that in Example 1. The difference is that in step 3), the mass content of VC in the electrolyte is 3%, the mass content of MMDS is 1.55%, the mass content of EMC is 51.45%, and the others remain unchanged.

[0150] Example 21

[0151] The battery preparation method in this embodiment is basically the same as that in Example 1. The difference is that in step 3), the mass content of VC in the electrolyte is 1%, the mass content of EMC is 54%, and the others remain unchanged.

[0152] Example 22

[0153] The battery preparation method in this embodiment is basically the same as that in Example 1. The difference is that in step 3), the mass content of VC in the electrolyte is 0.35%, the mass content of EMC is 54.65%, and the others remain unchanged.

[0154] Example 23

[0155] The battery preparation method in this embodiment is basically the same as that in Example 1. The difference is that in step 3), the mass content of MMDS in the electrolyte is 0.01%, the mass content of EMC is 53.99%, and the others remain unchanged.

[0156] Example 24

[0157] The battery preparation method in this embodiment is basically the same as that in Example 1. The difference is that in step 3), the mass content of LiPO2F2 in the electrolyte is 0.01%, the mass content of EMC is 53.49%, and the others remain unchanged.

[0158] Example 25

[0159] The battery preparation method in this embodiment is basically the same as that in Example 1. The difference is that in step 3), the mass content of TAPP in the electrolyte is 0.01%, the mass content of EMC is 53.49%, and the others remain unchanged.

[0160] Comparative Example 1

[0161] The battery preparation method in this comparative example is basically the same as that in Example 5. The difference is that in step 3), based on the total mass of the electrolyte, the mass content of EMC is 54.5% and the mass content of VC is 0.2%.

[0162] Comparative Example 2

[0163] The preparation method of the battery in this comparative example is basically the same as that in Example 5. The difference is that in step 3), based on the total mass of the electrolyte, the mass content of EMC is 53.5%, and there is no LiPO2F2 in the electrolyte.

[0164] Comparative Example 3

[0165] The battery preparation method in this comparative example is basically the same as that in Example 5. The difference is that in step 3), based on the total mass of the electrolyte, the mass content of EMC is 53.5%, and there is no TAPP in the electrolyte.

[0166] Comparative Example 4

[0167] The battery preparation method in this comparative example is basically the same as that in Example 5. The difference is that in step 3), based on the total mass of the electrolyte, the mass content of EMC is 51.35%, the mass content of VC is 3%, and the mass content of MMDS is 1.65%.

[0168] Comparative Example 5

[0169] The preparation method of the battery in this comparative example is basically the same as that in Example 5. The difference is that in step 3), based on the total mass of the electrolyte, the mass content of EMC is 54%, and there is no MMDS in the electrolyte.

[0170] Comparative Example 6

[0171] The preparation method of the battery in this comparative example is basically the same as that in Example 5. The difference is that in step 3), based on the total mass of the electrolyte, the mass content of EMC is 55%, and there is no VC in the electrolyte.

[0172] Comparative Example 7

[0173] The preparation method of the battery in this comparative example is basically the same as that in Example 5, except that in step 3), based on the total mass of the electrolyte, the mass content of EMC is 52% and the mass content of MMDS is 2%.

[0174] Comparative Example 8

[0175] The preparation method of the battery in this comparative example is basically the same as that in Example 5. The difference is that in step 3), based on the total mass of the electrolyte, the mass content of EMC is 52% and the mass content of LiPO2F2 is 1.5%.

[0176] Comparative Example 9

[0177] The battery preparation method in this comparative example is basically the same as that in Example 5, except that in step 3), based on the total mass of the electrolyte, the mass content of EMC is 52.5% and the mass content of TAPP is 1%.

[0178] The basic parameters are shown in Table 1.

[0179] Table 1

[0180]

[0181]

[0182] Test case

[0183] 1. The high-temperature cycling performance and high-temperature storage performance of the batteries prepared in the above embodiments and comparative examples were tested, including the following steps:

[0184] 1) High-temperature cycling performance

[0185] Place the battery at an ambient temperature of 45°C until the battery body temperature matches the ambient temperature. Then, charge it at a constant current and constant voltage rate of 0.5C to 4.25V, and then discharge it at a constant current rate of 0.5C to 2.5V. Record the initial charge capacity and discharge capacity. Cycle the battery according to the aforementioned charge and discharge steps until the capacity retention rate reaches 80%, and record the number of cycles. Excellent high-temperature cycling performance should meet the requirement of more than 1000 cycles.

[0186] 2) High-temperature storage performance

[0187] The battery was charged to 4.3V using a constant current and constant voltage of 0.33C, with a cutoff current of 0.05C. It was then discharged to 2.5V using a constant current of 0.33C, yielding the initial discharge capacity C0. The battery was then charged again to 4.3V using a constant current and constant voltage of 0.33C0, with a cutoff current of 0.05C0, resulting in a fully charged battery. This fully charged battery was placed in a 60°C constant temperature chamber, and its capacity was calibrated every 28 days. After 196 days of storage, the battery was discharged to 2.5V using a constant current of 0.33C0, yielding the remaining capacity C1. The previously discharged battery was then charged to 4.3V using a constant current and constant voltage of 0.33C0, with a cutoff current of 0.05C0, and then discharged to 2.5V using a constant current of 0.33C0. This charge-discharge cycle was repeated three times, and the discharge capacity of the third cycle was taken as the recovered capacity C1. 196 The capacity recovery rate (%) after 196 days of storage at 60℃ is calculated as follows: (C...) 196 -C0) / C0×100%. Excellent high-temperature storage performance should meet the requirement that the capacity recovery rate is greater than 80% after 196 days of storage.

[0188] 3) Gas production

[0189] Using Archimedes' principle, the battery is suspended by a dynamometer, and the dynamometer obtains a pulling force F0. Then, the battery is completely immersed in water, and the dynamometer obtains a pulling force F1. After storing for a certain number of days, the battery is suspended by a dynamometer and immersed in water again, and the dynamometer obtains a pulling force F2. At this time, the increase in unit capacity volume of the battery is V(mL / Ah)=(F1-F2) / 9.8C0, where C0 is the initial discharge capacity of the battery obtained from the above test.

[0190] The test results are shown in Table 2.

[0191] Table 2

[0192]

[0193]

[0194] From Table 1 and Table 2, we can see that:

[0195] Compared to Comparative Examples 1-9, the batteries in Examples 1-25 exhibit higher cycle performance, storage performance, and lower gas production. The battery in Example 3, in particular, achieved 1425 cycles at 45°C and maintained a capacity recovery rate of 85.5% after 196 days of storage at 60°C, with a gas production of only 0.91. This demonstrates that the electrolyte exhibits high stability under high-voltage conditions, effectively improving the battery's cycle and storage performance.

[0196] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An electrolyte, characterized in that, The electrolyte comprises lithium salt, organic solvent, and additives; the additives include unsaturated carbonate additives, sulfur-based additives, lithium difluoride salt additives, and unsaturated phosphate ester additives. Based on the total mass of the electrolyte, the mass content m1% of the unsaturated carbonate additives satisfies: 0.35≤m1≤3.0, the mass content m2% of the sulfur-based additives satisfies: 0.01≤m2≤1.5, the mass content m3% of the lithium difluoride salt satisfies: 0<m3≤1.0, and the mass content m4% of the unsaturated phosphate ester additives satisfies: 0.01≤m4≤0.

8. The electrolyte satisfies: y = 0.35b 2 -2.10b+4.04, and 0.89≤y≤3.2, where b is the total mass content of the additive in the electrolyte, in percentages (%).

2. The electrolyte according to claim 1, characterized in that, 1.5≤m1≤3.0, and / or, 0.5≤m2≤1.5, and / or, 0.5≤m3≤1.0, and / or, 0.3≤m4≤0.8, and / or, 0.89≤y≤2.

0.

3. The electrolyte according to claim 1 or 2, characterized in that, The unsaturated carbonate additives include vinylene carbonate; And / or, the sulfur-based additives include at least one of methylene disulfonate, vinyl sulfate, 1,3-propenesulfonate lactone, and propylene sulfite. And / or, the lithium difluorophosphate additive includes at least one of lithium difluorophosphate, lithium difluorosulfonylimide, and lithium difluorooxalate phosphate; And / or, the unsaturated phosphate additives include triargyl phosphate and / or triallyl phosphate.

4. The electrolyte according to any one of claims 1-3, characterized in that, The additives also include fluorocarbonate additives and / or cyclic carbonate additives; Preferably, the fluorocarbonate additives include fluoroethylene carbonate and / or fluoroethylene carbonate; Preferably, the cyclic carbonate additive includes ethylene carbonate.

5. The electrolyte according to claim 4, characterized in that, Based on the total mass of the electrolyte, the mass content m5% of the fluorocarbonate additives and / or cyclic carbonate additives satisfies: 0 < m5 ≤ 0.

5.

6. The electrolyte according to any one of claims 1-5, characterized in that, 0.35%≤b≤4.7%。 7. The electrolyte according to any one of claims 1-6, characterized in that, The lithium salt includes lithium hexafluorophosphate; preferably, the lithium salt further includes lithium bis(trifluoromethanesulfonyl)imide and / or lithium dioxaborate; preferably, the lithium salt has a mass content of 12% to 15% in the electrolyte.

8. The electrolyte according to any one of claims 1-7, characterized in that, The organic solvent includes a first carbonate solvent; preferably, the first carbonate solvent includes ethylene carbonate.

9. The electrolyte according to claim 8, characterized in that, The organic solvent in the electrolyte has a mass content of 80% to 86%; and / or, the ethylene carbonate in the electrolyte has a mass content of 20% to 30%.

10. The electrolyte according to claim 7 or 8, characterized in that, The organic solvent also includes a second carbonate solvent, which includes at least one of methyl ethyl carbonate, dimethyl carbonate, and diethyl carbonate.

11. A battery, characterized in that, The battery includes the electrolyte as described in any one of claims 1-10.

12. The battery according to claim 11, characterized in that, The battery further includes a positive electrode sheet, which includes a positive electrode active material; the positive electrode active material includes a ternary material and a lithium manganese iron phosphate material; preferably, the mass ratio of the ternary material and the lithium manganese iron phosphate material is 2:8 to 8:

2.

13. The battery according to claim 11 or 12, characterized in that, The battery further includes a negative electrode sheet, which includes a negative electrode active material; the negative electrode active material includes a carbon-based negative electrode material, which includes at least one of artificial graphite, natural graphite, hard carbon, soft carbon, and mesophase carbon microspheres.

14. A battery pack, characterized in that, The battery pack includes at least two batteries as described in any one of claims 11-13.

15. An electrical appliance, characterized in that, The electrical equipment includes the battery as described in any one of claims 11-13, or the battery pack as described in claim 13.